Analisis Kerusakan Permukaan Aspal pada Ruas Jalan Akuila Raya Wayame Kota Ambon - Mataheru, Afreldo Benjamin; Siahaya, Vera Th. C.; Lewakabessy, Godfried (JURNAL ILMIAH NUSANTARA, 2025)
The Akuila Raya Wayame Road section in Ambon City, which is in Ambon Bay, Maluku Province, with a road length of 820 m, a road width of 12.6 m, the condition of the road on this section was several types of damage encountered, such as holes, surface roughness, loose grain, sagging, peeling of the surface layer, wear and tear. This results in complex problems and many losses, especially for road users. The purpose of this writing is to analyze and determine road damage on the Jalan Akuila Raya Wayame section, Ambon City and plan the cost budget for the Jalan Akuila Raya Wayame section, Ambon City. To determine the value of road conditions, the efforts that can be made and the Draft Budget (RAB) to improve road conditions are carried out using the Binamarga method to assess road conditions. The research results show that the percentage of LHR on road sections is that motorbikes (Group 1) dominate daily traffic, namely 2,073 vehicles or 82.68%, followed by private cars (Group 3), namely 390 vehicles or 15.55%. each point is 39.02%.